Peran Pemerintah dan Manajemen Pemasaran Terhadap Keberlanjutan Usaha Mikro, Kecil dan Menengah UMKM Di Tepi Laut Tanjungpinang - Putri Dwi Novrina; Gusman; Ahwe Eliza Nanda; Arianto Saputra Daeli; Handoko Handoko; Hendi Gunawan; Jeksen Jeksen; Michael Fernando (Politeknik Raflesia Press, 2025)
Seaside MSMEs in Tanjungpinang Kota District are more than just a place to shop. There, visitors can enjoy various amusement rides and musical performances that attract the attention of local people and tourists. The development of MSMEs cannot be separated from the support of the government, and the sustainability of MSMEs must be realized in order to increase state income, but for the sustainability of MSMEs it must also be supported by MSME actors in how they must maintain their business so that liquidation does not occur. This research uses descriptive qualitative methods by clarifying roles and others to obtain interview results by the sea. The government is tasked with establishing clear policies, MSMEs that open on the Tanjung Pinang waterfront must apply for permits, obtain stalls for free, and utilize existing facilities in the form of electricity, lighting and cleaning facilities. Electricity use for MSMEs depends on how many lamps are used, owners of electric cars which are usually rented to customers have experienced a separate increase in electricity rates. The use of electricity in MSMEs depends on how much electricity they use, one of which is the usual electric car business. Marketing management is still in line with what has been stated by Barnlund Johannessen, namely interpersonal communication, the reputation of MSME actors is an attraction because the food that MSME actors sell is of high quality, the length of time the activity lasts.